Acute administration of high doses of taurine does not substantially improve high-intensity running performance and the effect on maximal accumulated oxygen deficit is unclear - Milioni, Fabio; Malta, Elvis de Souza; Rocha, Leandro George Spinola do Amaral; Mesquita, Camila Angélica Asahi; de Freitas, Ellen Cristini; Zagatto, Alessandro Moura (Canadian Science Publishing, 2016)
The aim of the present study was to investigate the effects of acute administration of taurine overload on time to exhaustion (TTE) of high-intensity running performance and alternative maximal accumulated oxygen deficit (MAODALT). The study design was a randomized, placebo-controlled, crossover design. Seventeen healthy male volunteers (age: 25 ± 6 years; maximal oxygen uptake: 50.5 ± 7.6 mL·kg(-1)·min(-1)) performed an incremental treadmill-running test until voluntary exhaustion to determine maximal oxygen uptake and exercise intensity at maximal oxygen uptake. Subsequently, participants completed randomly 2 bouts of supramaximal treadmill-running at 110% exercise intensity at maximal oxygen uptake until exhaustion (placebo (6 g dextrose) or taurine (6 g) supplementation), separated by 1 week. MAODALT was determined using a single supramaximal effort by summating the contribution of the phosphagen and glycolytic pathways. When comparing the results of the supramaximal trials (i.e., placebo and taurine conditions) no differences were observed for high-intensity running TTE (237.70 ± 66.00 and 277.30 ± 40.64 s; p = 0.44) and MAODALT (55.77 ± 8.22 and 55.06 ± 7.89 mL·kg(-1); p = 0.61), which seem to indicate trivial and unclear differences using the magnitude-based inferences approach, respectively. In conclusion, acute 6 g taurine supplementation before exercise did not substantially improve high-intensity running performance and showed an unclear effect on MAODALT.
Keywords: anaerobic capacity; capacité anaérobie; EPOC; exercice d’intensité élevée; high-intensity exercise; lactate; MAOD